2013
DOI: 10.1108/ijsms-14-04-2013-b002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of team identification, e-service quality (e-SQ) and satisfaction on intention to revisit sports websites

Abstract: With the emergence of new technologies, the importance of e-service quality is being emphasised by sports marketing practitioners, who are focusing their efforts on improving how sports fans perceive, and are satisfied by, e-services (Loakimidis, 2010). Along with the importance of e-service quality, team identification is receiving a great deal of attention by sports marketing researchers, in order to home in on the different levels of sports fans' involvement with their team. However, few research efforts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
3
23
0
2
Order By: Relevance
“…Only mediated by the perceived value, team identification could predict purchase intention. Suh, Ahn, and Pedersen (2013) found the effect of team identification on e-service quality, satisfaction, and revisit intention focusing on the sports websites. Moreover, previous studies have also found a positive impact of team identification on actual attendance (Fisher & Wakefield, 1998;Laverie & Arnett, 2000;Murrell & Dietz, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Only mediated by the perceived value, team identification could predict purchase intention. Suh, Ahn, and Pedersen (2013) found the effect of team identification on e-service quality, satisfaction, and revisit intention focusing on the sports websites. Moreover, previous studies have also found a positive impact of team identification on actual attendance (Fisher & Wakefield, 1998;Laverie & Arnett, 2000;Murrell & Dietz, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…Several researchers have investigated online consumers' perceptions of website quality, specifically e-service quality (e.g., Li, Tan, & Xie, 2002;Ranganathan & Ganapathy, 2002;Negash, Ryan, & Igbaria, 2003;Santos, 2003). More recent studies have developed the conceptualization of quality of sport websites and measured it in additional ways (Gonzalez, et al, 2015;Suh & Pedersen, 2010;Hur, et al, 2011;Suh, et al, 2013). Gonzalez, et al (2015) argued that sport websites quality need to be assessed in a comprehensive way as sport team websites are usually informative and multi-functional to fulfill users' need.…”
Section: Sport Website Qualitymentioning
confidence: 99%
“…Hence, sport website quality has multiple facets as an extension of sports organizations. Sport website quality can be characterized as a multifaceted construct composed of several distinct but related facets, such as information, interaction, design, system, and fulfillment, each of which taps one facet of the overall construct to assess sport consumers' perception of quality (Hur, Ko, & Valacich, 2011;Suh, Ahn, & Pedersen, 2013). However, in the multifaceted construct of sport website quality, the central scientific interest lies primarily in the general construct but not the underlying constructs (i.e., information, interaction, design, system, and fulfillment).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that researchers may want to investigate complicated relationships among various constructs in terms of consumer behaviors (i.e., service quality, perceived value, consumer satisfaction, and behavioral intentions), structural equation modeling (SEM) has been used in sport industry research (Kim, Kim, Park, Yoo, & Kwon, 2014;Ko, Zhang, Cattani, & Pastore, 2011;Suh, Ahn, & Pedersen, 2013). Given that the current research investigated consumer behaviors of virtual golf, which has had little attention so far, a structural equation modeling (SEM) could be an appropriate statistical procedure examine their consumption propensities.…”
Section: Structural Equation Modelingmentioning
confidence: 99%